2020
DOI: 10.21203/rs.3.rs-80146/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Tocilizumab an effective therapy for Severe COVID-19: a retrospective cohort study

Abstract: ObjectivesTo compare the outcome of severe COVID-19 patients treated with Tocilizumab (TCZ). Methods: A retrospective cohort study comparing the clinical characteristics and outcomes of patients who received TCZ with those who did not, was conducted at The Indus Hospital, Karachi. A sub-group analysis was conducted on the TCZ group to identify predictors of mortality. Results 88 patients including 41 patients in the TCZ group and 47 in non-TCZ group were recruited. Baseline characteristics were comparable. TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Some observational studies have reported mortality benefit of TCZ [37,38] but RCTs failed to demonstrate any difference in survival when compared to placebo or usual care [39]. Data from our center also did not show any survival benefit of TCZ [40]. The final model showed that the factors associated with mortality are older age, low oxygen saturation, high SOFA scores, raised pro-calcitonin, ICU admission and sepsis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Some observational studies have reported mortality benefit of TCZ [37,38] but RCTs failed to demonstrate any difference in survival when compared to placebo or usual care [39]. Data from our center also did not show any survival benefit of TCZ [40]. The final model showed that the factors associated with mortality are older age, low oxygen saturation, high SOFA scores, raised pro-calcitonin, ICU admission and sepsis.…”
Section: Discussionmentioning
confidence: 75%
“…Some observational studies have reported mortality benefit of TCZ [37, 38] but RCTs failed to demonstrate any difference in survival when compared to placebo or usual care [39]. Data from our center also did not show any survival benefit of TCZ [40].…”
Section: Discussionmentioning
confidence: 80%
“…Some observational studies have reported mortality benefit of TCZ [ 40 , 41 ] but RCTs failed to demonstrate any difference in survival when compared to placebo or usual care [ 42 ]. Data from our center also did not show any survival benefit of TCZ [ 43 ].…”
Section: Discussionmentioning
confidence: 99%